Energetic and exergetic analyses of a combined system consisting of a high-temperature polymer electrolyte membrane fuel cell and a thermoelectric generator with Thomson effect. (21st June 2019) - Guo, Xinru; Zhang, Houcheng; Yuan, Jinliang; Wang, Jiatang; Zhao, Jiapei; Wang, Fu; Miao, He; Hou, Shujin
Abstract: A combined system model consisting of a high-temperature polymer electrolyte membrane fuel cell (HT-PEMFC), a regenerator and a thermoelectric generator (TEG) is proposed, where the TEG is applied to harness the generated waste heat in the HT-PEMFC for extra electricity production. The TEG considers not only the Seebeck effect and Peltier effect but also the Thomson effect. The mathematical expressions of power output, energy efficiency, exergy destruction rate and exergy efficiency for the proposed system are derived. The energetic and exergetic performance characteristics for the whole system are revealed. The optimum operating ranges for some key performance parameters of the combined system are determined using the maximum power density as the objective function. The combined system maximum power density and its corresponding energy efficiency and exergy efficiency allow 19.1%, 12.4% and 12.6% higher than that of a stand-alone HT-PEMFC, while the exergy destruction rate density is only increased by 8.6%. The system performances are compared between the TEG with and without the Thomson effect. Moreover, the impacts of comprehensive parameters on the system performance characteristics are discussed. The obtained results are helpful in developing and designing such an actual combined system for efficient and clean power production. Highlights: TEGs are proposed as a waste heat recovery technology for HT-PEMFCs. Thermal-electrochemical losses within the proposed system are described. Performance parameters evaluating the proposed system are obtained. The proposed system is effective for waste heat recovery. Effects of some design parameter and operating conditions are revealed.